2011
DOI: 10.1111/j.1567-1364.2011.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological structuring of yeasts associated with trees around Hamilton, Ontario, Canada

Abstract: This study seeks to determine the distribution and diversity of yeasts in and around the Hamilton area in Canada. In light of the increasing number of fungal infections along with rising morbidity and mortality rates, especially among the immunocompromised, understanding the diversity and distribution of yeasts in natural environments close to human habitations has become an increasingly relevant topic. In this study, we analyzed 1110 samples obtained from the hollows of trees, shrubs and avian droppings at 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 52 publications
3
42
2
Order By: Relevance
“…These rates remain lower than Saccharomyces isolation success in British Columbia, Germany, Portugal (33% on Fagaceae and 9% on other trees; Sampaio & Goncalves, 2008) and Pennsylvania (23% on Fagaceae; Sniegowski et al, 2002), but are equivalent to what was observed in UK (8% on Fagaceae; Johnson et al, 2004) and Ontario (10% on Fagaceae and 4% on other trees; Maganti et al, 2012). These rates remain lower than Saccharomyces isolation success in British Columbia, Germany, Portugal (33% on Fagaceae and 9% on other trees; Sampaio & Goncalves, 2008) and Pennsylvania (23% on Fagaceae; Sniegowski et al, 2002), but are equivalent to what was observed in UK (8% on Fagaceae; Johnson et al, 2004) and Ontario (10% on Fagaceae and 4% on other trees; Maganti et al, 2012).…”
Section: Saccharomycetaceae and Saccharomyces Diversitymentioning
confidence: 70%
“…These rates remain lower than Saccharomyces isolation success in British Columbia, Germany, Portugal (33% on Fagaceae and 9% on other trees; Sampaio & Goncalves, 2008) and Pennsylvania (23% on Fagaceae; Sniegowski et al, 2002), but are equivalent to what was observed in UK (8% on Fagaceae; Johnson et al, 2004) and Ontario (10% on Fagaceae and 4% on other trees; Maganti et al, 2012). These rates remain lower than Saccharomyces isolation success in British Columbia, Germany, Portugal (33% on Fagaceae and 9% on other trees; Sampaio & Goncalves, 2008) and Pennsylvania (23% on Fagaceae; Sniegowski et al, 2002), but are equivalent to what was observed in UK (8% on Fagaceae; Johnson et al, 2004) and Ontario (10% on Fagaceae and 4% on other trees; Maganti et al, 2012).…”
Section: Saccharomycetaceae and Saccharomyces Diversitymentioning
confidence: 70%
“…In North America, S. paradoxus is sympatric with its sister species Saccharomyces cerevisiae, although S. cerevisiae seems to be less common or absent at higher latitudes [20,21], where temperatures are cooler (see electronic supplementary material, figure S2a,b). This distribution is in agreement with previous observations that S. paradoxus is able to grow at lower temperatures than its sister species [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Eleven of the isolated species formed a group with Candida lignohabitans. This yeast has been isolated from the gastrointestinal tract of insects of the order Coleoptera, and formed a group together with Candida shehatae and Sugiyamaella sp (Houseknecht et al, 2011), isolated from hollow portions of cotton stems (Maganti et al, 2012) and forest plants (Kurtzman, 2007). These authors have described the isolation of the species, while not commenting on its physiological characteristics or biotechnological applications.…”
Section: Discussionmentioning
confidence: 99%